PENGELOLAAN SUPERVISI PEMBELAJARAN BERBASIS MUTU (Studi Situs SMK PGRI 6 Ngawi Tahun 2009/2010) - WIKANSO, WIKANSO (2011)
This study aimed to describe the learning management supervision by the Head of Vocational High School PGRI 6 Ngawi with focus on the process of supervision and the use of supervised learning techniques. The approach in this research is qualitative ethnographic methods. In this study, researchers participate in a cultural environment under study, studying, recording and collecting the necessary data. The desired data in this study is about the supervision process of learning and the use of supervised learning techniques in Vocational High School PGRI 6 Ngawi. Sources of data in this study were headmaster, vice headmaster, and teachers. Methods of data collection is in-depth interviews, participating observation and study of documentation, further data analysis technique is the reduction of data from data collection, data display and conclusion. The results of this study indicate that 1) the learning process of supervision, Vocational High School Head PGRI 6 Ngawi done in three stages, namely planning, implementation and evaluation. Supervision process is basically implements the functions of management, planning, organizing, directing, coordinating, and controlling/evaluating. By applying management functions in the process of supervision, the supervision activities to be focused, organized, coordinated and controlled, thus enabling the achievement of objectives. 2) Use of supervised learning techniques based on the types of problems faced by teachers, individual techniques used were classroom observation, individual conferences, classroom visitation, and the technical character of the group is for the new teacher orientation, demonstration teaching, teacher meetings, directed reading and upgrading. With the application of appropriate techniques of supervision problems, it will be able to help overcome the problems faced by teachers in an effective and efficient.